ASSESSMENT OF LYMPHOCYTE DNA DAMAGE IN BREAST CANCER AND ITS ASSOCIATION WITH AGE AND MENOPAUSAL STATUS: A STUDY AMONG TAMIL WOMEN. - A. SHEEBA CHRISTINA (International Journal of Pharma and Bio Sciences, 2013)
Breast cancer development is intimately related to DNA damage and DNA repair failures. The aim of this study was to investigate the level of DNA damage in the lymphocytes of breast cancer patients and to find its association with age and menopausal status. This study comprises of 75 breast cancer patients, equally categorized into three groups, based on the disease stage namely, non metastatic group, metastatic group and post treatment group. Control consisted of 25 healthy subjects. Lymphocytes were isolated from blood samples and DNA damage was assessed by comet assay. DNA damage was remarkably higher in breast cancer patients than in healthy subjects. Increased DNA damage was found in patients with metastases and post-treatment group. A positive correlation has been obtained in case of age and DNA damage. DNA damage was also high in post menopausal group when compared with pre menopausal group. These findings reveal that DNA damage increases with disease progression. DNA damage was also found to be positively associated with age and menopausal status of women with breast cancer. This stronger correlation observed may be useful in elucidating the mechanism of disease pathogenesis.